Anxious decades : America in prosperity and depression, 1920 - 1941 - Parrish, Michael E. (Norton twentieth century America series, 1992)
This is the story of the United States between 1920 and 1942, a time when the country soared higher and fell lower than at any period in its short history. In these convulsive years, Americans were dazzled by the pleasures of unprecedented economic prosperity and beset by the worst depression in their history. It was the era of Model T's, rising incomes, scientific management, electricity, talking movies, and advertising techniques that sold a seemingly endless stream of